122 Influence of diabetes and obesity on mortality and sternal wound complications after coronary artery bypass graft surgery: ten-year follow-up from the arterial revascularisation trial. (17th July 2020) - Flather, Marcus; Stefil, Maria; Taggart, David; Podesser, Bruno; Benedetto, Umberto; Gaudino, Mario; Gerry, Stephen; Gray, Alastair; Lees, Belinda; Krzych, Lukasz
Abstract : Background: Diabetes is associated with higher risk of mortality in patients undergoing coronary artery bypass graft (CABG) but the effects of obesity, and the interactions between diabetes and obesity in the context of CABG, have not been fully explored. Methods: The Arterial Revascularisation Trial (ART) randomised patients to single- or bilateral internal thoracic arterial graft plus other vein or arterial grafts as needed and followed them for 10 years to compare mortality, clinical outcomes and safety. In this analysis we explored the effects of diabetes and obesity on mortality and risk (sternal wound complications) . Diabetes was defined according to clinical history at baseline and combined insulin and non-insulin dependent patients, and obesity was defined as body mass index (BMI) ≥30kg/m2 at baseline. Results: Data on diabetes, obesity and ten-year mortality were available for 3094 patients who were included in the analysis. Mean age was 64 years, 86% male, mean weight 82kg and BMI 28. Diabetes was documented in 24% and obesity in 30% and as expected obese patients were more likely to be diabetic. The hazard ratios (95% confidence intervals) for ten-year mortality using the no-diabetes, non-obese group as a reference were 1.33 (1.08, 1.64) (diabetes, non-obese), 0.93 (0.75, 1.16) (no diabetes, obese) and 1.18 (0.91, 1.54) (diabetes, obese) groups (Figure ). Similar patterns of risk were observed whether patients were randomised to receive single or bilateral internal thoracic arteries and diabetes appeared to be the main driver of elevated risk of early sternal wound complications following CABG. Conclusions: Obesity and diabetes often occur in the same patients, but our analysis shows that patterns of risk of death after CABG are not additive for these characteristics, and obesity may actually be associated with lower death rates in patients with and without diabetes. Sternal wound complications appeared to be driven more by diabetes than obesity. Further analyses will be presented to explore the possible mechanisms for these observations. Conflict of Interest: None